2008
DOI: 10.1070/pu2008v051n08abeh006600
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-modified gravities and massive gravitons

Abstract: We review some theoretical and phenomenological aspects of massive gravities in 4 dimensions. We start from the Fierz--Pauli theory with Lorentz-invariant mass terms and then proceed to Lorentz-violating masses. Unlike the former theory, some models with Lorentz-violation have no pathologies in the spectrum in flat and nearly flat backgrounds and lead to interesting phenomenology.Comment: 81 page, 2 postscript figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
372
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(381 citation statements)
references
References 133 publications
(280 reference statements)
6
372
0
3
Order By: Relevance
“…Massive gravity in 4-dimensional spacetimes have been intensively studied recently, see, for example, [43] and references therein). Then, it can be shown that the equation for the metric perturbation ψ k in the Minkowski background reads, ψ k + ω 2 k ψ k = 0, but now with…”
Section: Discussionmentioning
confidence: 99%
“…Massive gravity in 4-dimensional spacetimes have been intensively studied recently, see, for example, [43] and references therein). Then, it can be shown that the equation for the metric perturbation ψ k in the Minkowski background reads, ψ k + ω 2 k ψ k = 0, but now with…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been realized that the dRGT construction opens the door to building theories with multiple interacting spin-2 particles [655,658]. In what follows, we will consider Lorentz invariant theories of massive gravity, but much work has been done on Lorentz violating theories [659][660][661][662][663][664][665][666][667][668][669][670][671][672][673][674].…”
Section: A Brief History Of Massive Gravitymentioning
confidence: 99%
“…We call such theories as the massive gravity or the bimetric gravity following N. Rosen [1]. Recently they have got a revival [30,31,32,33]. Given metric f µν and embedding variables e α (t, x k ) we are to treat N(t, x k ), N i (t, x k ), η ij (t, x k ) as the known functions.…”
Section: Hamiltonian Approach To Massive Gravitymentioning
confidence: 99%